Case report: Genomic screening for inherited cardiac conditions in Ecuadorian mestizo relatives: Improving familial diagnose - Cadena-Ullauri, Santiago; Guevara-Ramirez, Patricia; Ruiz-Pozo, Viviana; Tamayo-Trujillo, Rafael; Paz-Cruz, Elius; Sánchez Insuasty, Tatiana; Doménech, Nieves; Ibarra-Rodríguez, Adriana Alexandra; Zambrano, Ana Karina (Frontiers in Cardiovascular Medicine, 2022)
Introduction Genomic screening is an informative and helpful tool for the clinical management of inherited conditions such as cardiac diseases. Cardiac-inherited diseases are a group of disorders affecting the heart, its system, function, and vasculature. Among the cardiac inherited abnormalities, one of the most common is Wolff-Parkinson-White syndrome. Similarly, hypertrophic cardiomyopathy is another common autosomal dominant inherited cardiac disease. Hypertrophic cardiomyopathy is associated with an increased incidence of Wolff-Parkinson-White syndrome; reports have suggested that it could be caused by a mutation in the protein-coding gene PRKAG2, which encodes a subunit of the AMP-activated protein kinase. Case presentation A 37-year-old Ecuadorian male (Subject A) with familiar history of bradycardia, cardiac pacemaker implantation, and undiagnosed cardiac conditions began with episodes of tachycardia, dizziness, shortness of breath, and a feeling of fainting. He was diagnosed with hypertrophic myocardiopathy and Wolff Parkinson White preexcitation syndrome. Furthermore, his cousin's son, an 18-year-old Ecuadorian male (Subject B), started suffering from migraine and tachycardia at any time of the day. He was diagnosed with hypertrophic myocardiopathy; his electrocardiogram showed a systolic overload. Next-generation sequencing and ancestry analyses were performed. A c.905G>A p.(Arg302Gln) mutation in the gene PRKAG2 and a mainly European composition were identified in both subjects. Conclusion Genetic testing is a valuable tool as it can provide important information regarding a disease, including its cause and consequences, not only for single individuals but to identify at-risk relatives. Furthermore, NGS results could guide the physician into targeted therapy. In the present case report, a missense pathogenic Arg302Gln mutation in the PRKAG2 gene has been identified in two related Ecuadorian Subjects diagnosed with hypertrophic myocardiopathy and Wolff-Parkinson-White. The variant has not been reported in Latin America; hence, this is the first report of the Arg302Gln mutation in the PRKAG2 gene in mestizo Ecuadorian subjects with mainly European ancestry components.